Distribution of ammonia-oxidizing archaea and bacteria in plateau soils across different land use types - Zhang, Jingxu; Dai, Yu; Yilin Wang; Wu, Zhen; Xie, Shuguang; Yong Liu (APPLIED MICROBIOLOGY AND BIOTECHNOLOGY, 2015)
Ammonia oxidation is known to be performed by both ammonia-oxidizing archaea (AOA) and bacteria (AOB), although their relative significance to nitrification process in soil ecosystems remains controversial. The distribution of AOA and AOB in plateau soils with different land use types and the influential factors remains unclear. The present study investigated the abundance and structure of AOA and AOB communities in upland soils adjacent to Erhai Lake in the Yunnan Plateau (China). Quantitative PCR assays indicated a large variation in the community size of AOA and AOB communities, with the numerical dominance of AOA over AOB in most of soils. Clone library analysis illustrated a marked shift in the structure of soil AOA and AOB communities. A high abundance of Nitrososphaera- and Nitrosotalea-like AOA was observed, while Nitrosospira-like species predominated in AOB. AOA and AOB abundance was positively influenced by total nitrogen and moisture content, respectively. Moreover, moisture content might be a key determinant of AOA community composition, while C/N and nitrate nitrogen played an important role in shaping AOB community composition. However, further efforts will be necessary in order to elucidate the links between soil AOA and AOB and land use.